Bringing live music to the main stage: a neighborhood analysis of music venues and their surrounding areas - Conner, Eric (Kansas State University, 2015)
Often cities are in a perpetual struggle to increase or maintain community development within their districts; how can cities revitalize struggling neighborhoods? How can cities bring energy and life into portions of the downtown? How can cities encourage development for night-time destinations? There is no clear-cut answer to these questions, but this study will examine what amenities within districts may be in the presence of successful music venues. I will determine the district-based criteria for potential venue placement for success based on multiple case studies of different venues located within St. Louis, MO; Omaha, NE; and Indianapolis, IN as described in Yin’s Case Study Research (2009). These case studies will be compared using the community capital framework (Green & Haines, 2012) using a matrix based upon a) social, b) physical, c) financial, and d) cultural capitals. Each study will contain both qualitative and quantitative analysis in order to tell the story of each district for more comprehensive analysis.
Keywords: Community Capital Framework; Neighborhood analysis; Live music venues; Area Planning and Development (0341)